Which features of AI-based tools are important for students? A choice-based conjoint analysis - Jörg von Garrel; Jana Mayer (Computers and Education: Artificial Intelligence)
AI-based language tools such as ChatGPT have the potential to fundamentally change studying and teaching at universities. Since there have been few empirical studies on the use of AI systems by students, this article aims to analyze the use of AI in higher education. In particular, it focuses on identifying features that are important to students when using AI during their studies. For this purpose, a choice-based conjoint experiment was conducted through a survey involving over 6300 participants from German universities. The results show that students attach particular importance to the degree of scientific rigor. The optimal package for an AI-based tool for studying includes the citation of reliable or truthful sources, the detection and correction of errors in the input, a comprehensive and detailed formulation of the output, no AI-caused hallucinations and transparency of the database. These characteristics differ only slightly in group-specific analyses.